1990
DOI: 10.1128/mcb.10.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen-induced DNA amplification in vitro: overreplication of the simian virus 40 origin region in extracts from carcinogen-treated CO60 cells.

Abstract: An in vitro system to study carcinogen-induced amplification in simian virus 40 (SV40)-transformed Chinese hamster (C060) cells is described. SV40 amplification in this system resembled in many aspects the viral overreplication observed in drug-treated C060 cells. Cytosolic extracts from N-methyl-N'-nitro-N-nitrosoguanidine-treated cells supported de novo DNA synthesis in the presence of excess exogenous T antigen and the SV40-containing plasmid pSVK,. (15,17,20,22,35,45). This process is regulated by cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…C060 cells were treated with MNNG 24 h after being seeded as previously described (4). Log-phase cells were plated at a density of 5 X 106/14-cm-diameter plate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C060 cells were treated with MNNG 24 h after being seeded as previously described (4). Log-phase cells were plated at a density of 5 X 106/14-cm-diameter plate.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously demonstrated that cytosolic extracts from permissive cells supplemented with purified T antigen efficiently replicate exogenous SV40 DNA templates containing a functional origin of replication, yielding complete closed circular DNA molecules (22,23,31,50,59), while extracts from Chinese hamster and other nonpermissive cell lines failed to support significant viral DNA replication (32 (4). Using the in vitro system, we have shown that partial replication of the SV40-containing plasmid is catalyzed by the carcinogentreated C060 cytosolic extracts, while HeLa extracts yielded full replication (4). The pattern of viral replication in the carcinogen-treated C060 extracts was unique, allowing restricted overreplication of the origin region (i.e., amplification), whereas distal sequences were not replicated significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A) in response to cell exposure to UV radiation and correlated this increase with DNA damage-induced viral DNA replication (28). Furthermore, cytosolic extracts from MNNG-treated SV40-transformed Chinese hamster cells supported SV40 DNA replication in vitro in the presence of exogeneous T antigen, whereas replication by extracts from untreated cells was inefficient (4). Treatment of irradiated cells with duplex oligonucleotides corresponding to the SV40 IR domain inhibited DNA amplification, presumably because the duplex oligonucleotides sequestered a DNA damage-activated factor needed for amplification in vivo (28).…”
mentioning
confidence: 99%
“…CO60 cells were treated with MNNG 24 h after being seeded as was previously described (Berko-Flint et al, 1990). Log phase cells were plated at a density of 5610 6 / 14 cm-diameter plate.…”
Section: Mnng Treatmentmentioning
confidence: 99%